2011
DOI: 10.1177/0269881110391832
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of donepezil in healthy young adults underline the fractionation of executive functioning

Abstract: The cholinergic system is involved in the modulation of both bottom-up and top-down attentional control. Top-down attention engages multiple executive control processes, but few studies have investigated whether all or selective elements of executive functions are modulated by the cholinergic system. To investigate the acute effects of the pro-cholinergic donepezil in young, healthy volunteers on distinct components of executive functions we conducted a double-blind, placebo-controlled, independent-groups desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
0
17
1
1
Order By: Relevance
“…Although the present study does not suggest any influence of varenicline on emotional processing or impulsivity, it showed cognitive-enhancing effects of varenicline on working and episodic declarative memory tasks, characteristic of cholinergic agents (Ginani et al, 2011;Rokem et al, 2010). As varenicline has no affinity for muscarinic receptors, the cognitive-enhancing effect of cholinergic agents may be at least partially mediated by nACh receptors.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although the present study does not suggest any influence of varenicline on emotional processing or impulsivity, it showed cognitive-enhancing effects of varenicline on working and episodic declarative memory tasks, characteristic of cholinergic agents (Ginani et al, 2011;Rokem et al, 2010). As varenicline has no affinity for muscarinic receptors, the cognitive-enhancing effect of cholinergic agents may be at least partially mediated by nACh receptors.…”
Section: Discussioncontrasting
confidence: 78%
“…In addition, varenicline increased n-back task performance among abstinent smokers , consistent with cognitive-enhancing effects of central cholinergic drugs including (A)Ch-esterase inhibitors donepezil and rivastigmine (Ginani et al, 2011;Rokem et al, 2010). Although their cholinergic effects are, in contrast to varenicline, not selective to nACh receptors, it could be hypothesized that varenicline has similar cognitive-enhancing effects.…”
Section: Introductionmentioning
confidence: 55%
“…To select the executive domains under investigation (see Ginani et al, 2011) we followed Miyake et al (2000) who showed that it is possible to dissociate executive domains including: updating, or changes of the content of working memory by deleting information that is no longer important to the task at hand and incorporation of new data; inhibition, the ability to inhibit distracting information when selecting relevant information; and shifting, the ability to alternate between different tasks. Dual-task performance, the ability to perform two tasks in parallel (Baddeley, Della Sala, Gray, Papagno, & Spinnler, 1997;Della Sala & Logie, 2001), did not associate to performance in the other domains (Miyake et al, 2000) and could thus constitute a separate cognitive entity (e.g., see Della Sala & Logie, 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Executive tasks (described as in Ginani et al, 2011) • Plus-minus task (see Miyake et al, 2000): a shifting measure consisting of three lists of 32 digits (the numbers 10-99 prerandomized without replacement). For the first list, the participants are instructed to add 3 to each number.…”
Section: Iq Alertness and Mood Measuresmentioning
confidence: 99%
“…In summary, RCTs with healthy individuals have been conducted mostly with donepezil (5 mg single dose or 5 mg/d). A single dose of 5 mg donepezil has been found to improve information processing [117,118], procedural, verbal and visual spatial memory [119-121] and some executive functions [122]. A positive effect of donepezil was found in voluntary but not involuntary attention in one study [123].…”
Section: Acetylcholine Esterase Inhibitorsmentioning
confidence: 99%